Self esteem and self concept assessment in adolescents a consideration for educacional orientation - Sánchez Crespo, Guadalupe (1997)
This study discusses the self-steem and self-concept perceived by Spanish adolescents through the Millon Adolescent Personality Inventoty (M.A.P.I.). The participants were 342/ 364 adolescent of both sexes between 13 and 18 years, divided into two age groups (13-15 and 16-18 years old). All scored significantly low in self-steeem or self-concept for their development. Results showed that these adolescents were socially unconfortable, annoyed with their school responsabilities, insecure, annoyed with their body image, emotionally weak and exhibited low academic achievement.